The classical guitar : a study in structural, technical and musical evolution - Nock, Howard James (Rhodes University, Faculty of Humanities, Department of Music, 1974)
Although complete works have been written dealing with the structural development of the guitar, to the best of my knowledge no attempt has yet been made to incorporate in one work an account in which structure, playing technique and musical style are correlated. Therefore the aim of this work has been to provide a compendium on these three main aspects of the historical development of the guitar ... The object of Part I is to try and establish the mainstream of the development of the guitar from the earliest beginnings of string instruments to the present day. Since little information and evidence of early instruments (i.e. before 1500 A.D.) is available, it has been necessary to formulate theories on how these developments may have taken place. Intro., p. 1.
Keywords: Guitar; Guitar -- Construction